The Comprehension of Counterfactual Conditionals: Evidence From Eye-Tracking in the Visual World Paradigm - Orenes, Isabel; García-Madruga, Juan A.; Gómez-Veiga, Isabel; Espino, Orlando; Byrne, Ruth M. J. (Frontiers in Psychology, 2019)
Three experiments tracked participants’ eye-movements to examine the time course of comprehension of the dual meaning of counterfactuals, such as “if there had been oranges then there would have been pears”. Participants listened to conditionals while looking at images in the visual world paradigm, including an image of oranges and pears that corresponds to the counterfactual’s conjecture, and one of no oranges and no pears that corresponds to its presumed facts, to establish at what point in time they consider each one. The results revealed striking individual differences: some participants looked at the negative image and the affirmative one, and some only at the affirmative image. The first experiment showed that participants who looked at the negative image increased their fixation on it within half a second. The second experiment showed they do so even without explicit instructions, and the third showed they do so even for printed words.